Analisis Pengaruh Investasi Asing Langsung (FDI), Investasi Dalam Negeri dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi Indonesia - Ayulia Putri, Jesi; Permata Cita, Fitria (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the influence of foreign direct investment (FDI), domestic investment (PMDN), and labor on Indonesia’s economic growth. This study uses secondary data sourced from the Indonesian Central Bureau of Statistics (BPS) for 2024. The research method used is a quantitative approach with cross-sectional data regression analysis. To obtain more reliable estimation results and address potential violations of classical assumptions, this study uses the robust standard error method. The results show that, partially, foreign direct investment (FDI) has a positive and significant effect on economic growth, while domestic investment (PMDN) has a significant negative effect. Meanwhile, the labor variable has no significant effect on economic growth. However, simultaneously, the variables FDI, PMDN, and labor are proven to have a significant effect on Indonesia’s economic growth. These findings indicate that investment plays a crucial role in driving economic growth, while the labor force requires quality improvement to optimize its contribution.